NEW METHODS OF MILK AND DAIRY PRODUCTS PROCESSING AND HEALTH EFFECTS - HAJIYEVA, BAHAR SABIR GIZI (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The purpose of this article is to analyze the technology of fermented dairy products, which is among the production technologies of milk and dairy products. As is well known, milk and dairy products are among the most important nutrients for growing, developing and leading a healthy lifestyle. In order to make the most of the important human qualities of milk, a number of technologies are used to increase its durability, protect the health of consumers and obtain various dairy products. Thanks to these rapidly developing production technologies from the past to the present, it has become possible to obtain more standard and high-quality milk and dairy products.The article examines milk and its composition, the importance of milk and dairy products for human health, the development of milk and dairy products, the main technologies of milk production, research in the field of fermented milk technology, written scientific works and articles on milk and dairy products. The information contained in the portals of the engaged enterprises was used. The article examines milk and its composition, the importance of milk and dairy products for human health, the development of milk and dairy products, the main technologies of milk production, research in the field of fermented milk technology, written scientific works and articles on milk and dairy products. The information contained in the portals of the engaged enterprises was used.The technologies used in the processing of milk and dairy products affect both the quality and consumption of these products, as well as the health of producers. Recently, new technologies used in the processing of milk and dairy products are considered important in terms of the quality of the products obtained. The article examines the features of these technologies, the processing process and the specifics of the products obtained. This is important for both researchers and consumers interested in dairy processing.As a result, it is noted that in recent years there has been a significant increase in interest in the impact of milk and dairy products on human health. Today, such products are called functional, that is, products that have an impact on health in addition to their nutritional value.It is emphasized that the technologies used to preserve the nutritional value of milk and clean it from bacteria harmful to human health are gradually developing. This increases the consumption of milk and dairy products and maximizes their health benefits.
Keywords: milk and dairy products; pasteurized milk production technologies; fermented milk products